Manoel Moises, Mãe Bela e o protestantismo rural na história da Igreja Presbiteriana em Cabeceira Grande-MG (1947-1970 - Flor, Lauana Ananias (2012)
The idea of a rural Protestantism is characterized by the relationship that believers has with ludic and its familiarity with the sacred. This kind of tupiniquim Protestantism, genuinely Brazilian, developed itself in places with low or absent catholic resistance, Brazilian s hegemonic religion, allowing inner arrangements that make it different from official Protestantism. This research tries to identify some features of that so-called rural Protestantism, mainly its interaction with popular traditional culture, in the context of the foundation of Cabeceira Grande (MG) s Presbyterian Church. Through oral and micro-history methodology, the focus of study will be next to the life of two important figures in this context: peasant Manoel Moises and midwife Mãe Bela. Protestant pioneer Manoel Moises arrives at the region in 1947, bringing its belongings in an oxcart. The origin of Cabeceira Grande s Presbyterian Church is due to the activities of this secular and autonomous preacher. Lately, with the religious community already formed, they receive visits of ministers of foreign missionary agencies acting in the region. As with Manoel Moises being a constant reference in local memory, Mãe Bela, one of the first Presbyterian converted of the community, is also remembered for its activities as midwife and its knowledge of traditional medicine, articulated with local religious imaginary. Also, Mãe Bela was donator of the terrain in which the temple of Presbyterian Church was built, in 1970.